Migration Policy in the Area of Border Control and Migration of the Population in OECD Countries –Theoretical and Practical Aspects - Woźniak, Katarzyna (Studia Historiae Oeconomicae, 2020)
The aim of the study is to present the phenomenon of population migration and migration policy as part of the state’s economic policy based on the example of OECD (Organization for Economic Cooperation and Development) countries, with particular emphasis on the area of migration policy, which is border control and related illegal migration. The temporal scope of the empirical analysis covers the period 1990-2016. The article consists of four main parts. The discussion began with a presentation of the balance of migration, the scale and dynamics of population immigration in OECD countries. Furthermore, the significance, areas and process of shaping migration policy as a part of the economic policy of the country are presented. Then, it focused on the migration policy in the area of border control in OECD countries. The discussion was crowned with the conclusions that followed.